Addressing social determinants of health and health promotion through Village Health, Sanitation and Nutrition Committee (VHSNC) in Odisha”. - Nayak, Susanta Kumar; Naik, Iswar Chandra (International Journal of Psychosocial Rehabilitation, 2020)
Health is the basic pre requisite for the existence of the human being. As defined by the World Health Organization, “Health is a state of complete physical, mental, and social well-being, not merely the absence of disease or infirmity”. A person’s health is the condition of their body and the extent to which it is free from illness or is able to resist illness. Health is a state in which a person is not suffering from any illness and is feeling well. The status of health is determined by the medico technical factors which are focused on treating the diseases, improved health infrastructure, quality Human Resources, quality health services, referral facility to the super speciality health institutions etc. However, besides the medical and technical factors, social factors play an equally vital role in determining the condition of health. Those factors are called as the social determinants of health.